2003
DOI: 10.1007/s00467-003-1284-0
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth with normal parathyroid hormone levels in chronic renal failure

Abstract: The optimum range for parathyroid hormone (PTH) levels in children with chronic renal failure (CRF) remains undefined. We aimed to determine growth velocity in children with CRF managed with normal PTH levels. We performed a retrospective case note review of 99 children (77 boys), with a glomerular filtration rate (GFR) <41 ml/min per 1.73 m(2), who had at least 2 years of 3-monthly follow-up. The age range at entry was 0.5-6.0 years; data collection was continued until 10 years of age or the commencement of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
2
37
0
3
Order By: Relevance
“…Height at the start of dialysis was significantly reduced, and was similar both to other studies from our unit, which showed infants and children with CRF or ESRF on dialysis or transplanted to have a HtSDS ranging from −1.73 to −2.9 [7][8][9], and to NAPTRCS data [3], which showed a HtSDS in the first month after initiation of dialysis of −1.99 at age 0-1 years, −2.05 at age 2-5, and −1.71 at age 6-12 years (−1.64 overall). However, despite this, growth was maintained in our patients, without further decline in HtSDS after starting dialysis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Height at the start of dialysis was significantly reduced, and was similar both to other studies from our unit, which showed infants and children with CRF or ESRF on dialysis or transplanted to have a HtSDS ranging from −1.73 to −2.9 [7][8][9], and to NAPTRCS data [3], which showed a HtSDS in the first month after initiation of dialysis of −1.99 at age 0-1 years, −2.05 at age 2-5, and −1.71 at age 6-12 years (−1.64 overall). However, despite this, growth was maintained in our patients, without further decline in HtSDS after starting dialysis.…”
Section: Discussionsupporting
confidence: 86%
“…We have shown that catch-up growth can be achieved with these regimens in children with CRF [7] and in infants and children on dialysis [8][9][10]. In this study we have looked at the effect of our policy on growth in prepubertal children on longterm dialysis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that intermittent calcitriol therapy combined with calcium-containing phosphate binders may adversely affect chondrocyte activity in the epiphyseal growth plate, with a consequent reduction in linear growth. Studies on the relations between adynamic bone, suppression of PTH with vitamin D therapies, and growth in children have yielded conflicting results [15][16][17].…”
Section: Histomorphometry Of Renal Osteodystrophymentioning
confidence: 99%
“…Serum parathyroid hormone (PTH) levels are used as a biomarker of bone turnover; however, current treatment recommendations are opinion based and controversial in pediatric patients with predialysis CKD (2,3). Some data suggest that optimal growth is associated with serum PTH levels within the normal range (4), whereas other studies have demonstrated the greatest growth velocity at higher PTH levels (5). Although PTH levels are currently used to guide therapy with active vitamin D sterols, little information exists as to the relationship between PTH and indices of bone turnover and mineralization in children with mild and moderate stages of CKD.…”
Section: Introductionmentioning
confidence: 99%